Dihydrogen vs. hydrogen bonding in the solvation of ammonia borane by tetrahydrofuran and liquid ammonia. Issue 17 (23rd April 2018) - Ingram, David J.; Headen, Thomas F.; Skipper, Neal T.; Callear, Samantha K.; Billing, Matthew; Sella, Andrea
Abstract : The solvation structures of two systems rich in hydrogen and dihydrogen bonding interactions have been studied in detail experimentally through neutron diffraction with hydrogen/deuterium isotopic substitution. Abstract : The solvation structures of two systems rich in hydrogen and dihydrogen bonding interactions have been studied in detail experimentally through neutron diffraction with hydrogen/deuterium isotopic substitution. The results were analysed by an atomistic Monte Carlo simulation employing refinement to the experimental scattering data. The systems studied were the hydrogen storage material ammonia borane (NH3 BH3, AB) dissolved in tetrahydrofuran (THF), and liquid ammonia (NH3 ), the latter in which AB shows unusually high solubility (260 g AB per 100 g NH3 ) and potential regeneration properties. The full orientational and positional manner in which AB–AB, AB–THF and AB–NH3 pairs interact with each other were successfully deciphered from the wide Q -range total neutron scattering data. This provided an unprecedented level of detail into such highly (di)hydrogen bonding solute–solvent interactions. In particular this allowed insight into the way in which H–B acts as a hydrogen bond acceptor. The (di)hydrogen bonding was naturally determined to dictate the intermolecular interactions, at times negating the otherwise expected tendency for polar molecules to align themselves with anti-parallel dipole moments. Several causes for the extreme solubility of AB in ammonia were determined, including the ability of ammonia to (di)hydrogen bond to both ends of the AB molecule and the small size of the ammonia molecule relative to AB and THF. The AB B–H to ammonia H dihydrogen bond was found to dominate the intermolecular interactions, occurring almost three times more often than any other hydrogen or dihydrogen bond in the system. The favourability of this interaction was seen on the bulk scale by a large decrease in AB clustering in ammonia compared to in the dihydrogen bond-less THF.